Alzheimer's Disease Detection Using Deep Learning : A Survey - Riham Mohamed Noureldin Salama Sadek (2024)
Abstract
Contents
Project (M.A.)$1 (BNile University, Egypt, 2024 .s
"Includes bibliographical references"
Text in English, abstracts in English.
Keywords: InformaticsIFM; Dissertation, Academic